SOCIAL COMMUNICATION OF ADDEWATANG PUTTA SERENG RITUAL IN BONE REGENCY - Bustan Kadir; Tuti Bahfiarti; Muhammad Farid (JURNAL ILMU BUDAYA, 2020)
The diversity that exists in Indonesia should be one of the reasons why communication is important to be studied, and depth analysed. Diversity will produce harmony when it managed by good communication and understanding. This study analysed social life in the Addewatang Putta Sereng ritual practised by a community in Bone Regency as a form of diversity. Focusing on communication behaviour in the Addewatang Putta Sereng ritual, this study would first (1) analysed religious messages, and subsequently (2) identify social communication in the Addewatang Putta Sereng ritual. This research used a qualitative method by using the ethnographic communication approach. Data were collected through in-depth interviews, observations, and documentation, then analysed using ethnographic data analysis. The results of this study indicated that the implementation of the Addewatang Putta Sereng ritual is a symbol of the belief (ateppekeng) and gratitude (asukkurukeng) of Ujung people towards the figure of Putta Sereng and God Almighty. Social communication in the Addewatang Putta Sereng ritual forms harmonious communication patterns, consisting of resistance and responsive communication practised by community groups that are resistant and conservative to the Addewatang Putta Sereng ritual.